2001
DOI: 10.1297/cpe.10.47
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Obese Japanese Children with Acanthosis Nigricans

Abstract: Acanthosis nigricans (AN) is a skin lesion characterized by thickening and obvious darkening of the keratin layer of the skin. It has been demonstrated to be associated with hyperinsulinemia, and is used as an empirical marker for elevated risk of type 2 diabetes. The prevalence of school children with simple obesity in Japan has recently increased to over 10%. We investigated the clinical characteristics of AN-positive and AN-negative subjects, and compared 105 obese children (64 males and 41 females) with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…It was not included in the diagnostic criteria for adults. The one associated with obesity is more usually expressed as ‘acanthosis’ rather than ‘pseudoacantosis’, and is a useful marker of insulin resistance even in children 19 . Thus, it was included as a ‘B problem’ in the present criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not included in the diagnostic criteria for adults. The one associated with obesity is more usually expressed as ‘acanthosis’ rather than ‘pseudoacantosis’, and is a useful marker of insulin resistance even in children 19 . Thus, it was included as a ‘B problem’ in the present criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The one associated with obesity is more usually expressed as 'acanthosis' rather than 'pseudoacantosis', and is a useful marker of insulin resistance even in children. 19 Thus, it was included as a 'B problem' in the present criteria. A single reference value for hyperuricemia was obtained from the recently published literature.…”
Section: Metabolic Derangement Related To Obesitymentioning
confidence: 99%
“…8,9 Although the rates of AN and obesity are different among races, a close association between these clinical findings and IR was documented in children from many countries and various ethnicities. 3,9,[10][11][12][13][14][15][16] The investigation of IR status requires a blood withdrawn under fasting condition and is associated with pain, patient's reluctance, and poor compliance. Thus, the clinical dermatological finding of AN may offer an easier solution to detect IR in obese children with better patient's compliance and parents acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral fat accumulation has been reported to increase insulin resistance through secretion of adipocytokines from fat cells(7, 8). Some Japanese studies have demonstrated insulin resistance associated with a compensatory increase of insulin secretion in obese children(9, 10). …”
Section: Introductionmentioning
confidence: 99%